Trans fatty acids content of biscuits commercially available in Malaysian market and comparison with other countries - M., Norhayati; Azlan, Azrina; Mohd Esa, Norhaizan; Razman, Muhammad Rizal (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
The fatty acid composition and trans fatty acid (TFA) contents of biscuits products were determined by gas chromatography, using a highly polar 100m capillary column (HP-88) and flame ionization detection. Total TFA ranged from 0.00 - 0.52 g/100 g total fatty acids and 0.12 - 0.68 g/100 g total fatty acids for local packed and unpacked biscuits, respectively. In imported biscuits, total TFA was higher ranging from 0.03 - 3.09 g/100 g of total fatty acids. Trans 16:1 was the most abundant, with values ranging from 0.01% to 38% followed by trans 18:1 Δ11 (0.01% - 13.11%), trans 18:1 Δ9 (0.01% - 4.68%), trans 18:2 (0.23% - 2.77%) and small quantities of trans 18:1 Δ6. CLA, the natural TFA constituted from 0.1% to <70% TFA. These results and comparison with published data indicate that Malaysian biscuits contained considerably low proportion of trans fatty acids following the wide use of palm fat.